Pola Penyelamatan Dan Perlindungan Satwa Endemik Riau Pasca Kebakaran Hutan Di Taman Nasional Tesso Nilo - Widia Edorita; Zulwisman Zulwisman (Riau Law Journal, 2021)
AbstractOne of the environmental problems is the reduced number of species found in living natural resources, especially rare plants and animals, which is accompanied by the destruction of the ecosystem. This also happens to biological resources and ecosystems in Riau province. Decreasing biodiversity in Riau Province is mainly due to forest conversion into plantations and forest and land fires which in the last 22 years have consumed nearly ¾ of Riau's forests. This certainly has a negative impact on the sustainability of biodiversity, especially endemic animals in Riau Province. Tesso Nilo National Park is an area with vascular plant diversity and is a habitat for endangered species, namely the Sumatran tiger (Panthera tigris sumatrae) and the Sumatran elephant (Elephas maximus sumatranus). This area was not spared from encroachment and conversion into plantations and settlements. Clearing forest land will result in the destruction of forest functions and result in the destruction of various types of flora and fauna. Efforts are made to continue various rescue patterns to minimize the erosion of biological resources, especially the elephants in Tesso Nilo National Park. Among these patterns and programs, some have been effective and some have not been due to several obstacles in their implementation.Keyword: rescue patterns-endemic animals-forest firesAbstrakSalah satu persoalan lingkungan hidup adalah berkurangnya jumlah species yang terdapat di dalam sumber daya alam hayati khususnya tumbuhan dan satwa langka yang disertai dengan rusaknya ekosistem. Hal ini juga terjadi pada sumber daya hayati dan ekosistem yang ada di provinsi Riau. Berkurangnya keanekaragaman hayati di Provinsi Riau terutama disebabkan oleh alih fungsi hutan menjadi perkebunan dan kebakaran hutan dan lahan yang dalam kurun waktu 22 tahun terakhir telah menghabiskan hampir ¾ hutan Riau. Hal ini tentu berdampak buruk bagi keberlanjutan keanekaragaman hayati terutama satwa endemik yang ada di Provinsi Riau. Taman Nasional Tesso Nilo merupakan kawasan dengan tingkat keanekaragaman tanaman berpembuluh dan merupakan habitat bagi satwa terancam punah yaitu harimau sumatera (Panthera tigris sumatrae) dan gajah sumatera (Elephas maximus sumatranus). Kawasan ini tidak luput dari kegiatan perambahan dan di konversi menjadi perkebunan dan permukiman. Pembukaan lahan hutan akan mengakibatkan rusaknya fungsi hutan dan mengakibatkan musnahnya berbagai jenis flora dan fauna. Berbagai pola penyelamatan terus diupayakan untuk meminimalkan tergerusnya  sumber daya alam hayati khususnya satwa gajah di Taman Nasional Tesso Nilo. Diantara pola dan program tersebut ada yang telah efektif dan ada juga yang belum dikarenakan adanya beberapa kendala dalam pelaksanaannya.